IMPROVING THE TACTICS OF MANAGING PREGNANT WOMEN WITH THE THREAT OF MISCARRIAGE UP TO 21 WEEKS OF GESTATION - Karimov , A.KH.; Aliyeva , M.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The article discusses tactics for managing pregnant women with the threat of miscarriage up to 21 weeks of gestation using micronized progesterone. A study was conducted involving 60 patients who were divided into two groups: with and without bleeding. The effectiveness of vaginal and rectal use of Fertigest and Cyclogest was assessed. The results of the study showed that vaginal use of progesterone showed slightly better results than rectal use, which allows us to clarify recommendations for the use of progesterone therapy in this group of patients